Material, method for producing material and electronic device

The material combines latent heat materials and thermally conductive materials in a specific composition and structure to address the challenge of achieving both high thermal conductivity and effective heat storage, resulting in enhanced heat dissipation performance for electronic devices.

JP2025051597APending Publication Date: 2025-04-04CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024102831
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-06-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Conventional composite materials face challenges in achieving both high thermal conductivity for efficient heat dissipation and effective heat storage, as the addition of high thermal conductivity materials often compromises heat storage capabilities.

Method used

A material comprising a plurality of particles formed from latent heat materials that undergo a solid-solid phase transition, combined with a thermally conductive material having a higher thermal conductivity, where the volume fraction of the thermally conductive material is 20% or more and less than 100%, and the average particle diameter of the latent heat material particles is 0.1 μm or more and 40 μm or less, forming a sea island structure for enhanced heat dissipation.

Benefits of technology

The proposed material achieves high heat dissipation performance while utilizing the heat storage capabilities of latent heat materials, effectively managing thermal density in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051597000001_ABST
    Figure 2025051597000001_ABST
Patent Text Reader

Abstract

To provide a material which efficiently radiates heat and a method for producing the same.SOLUTION: There is provided a material in which a plurality of particles formed by including a latent heat material which undergoes a solid-solid phase transition and a heat conductive material having a higher thermal conductivity than the latent heat material are mixed, wherein the heat-conductive material has a volume fraction of the material of 20% or more and less than 100% and the particles have an average particle diameter of 0.1 μm or more and 40 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a material, a method for producing the material, and an electronic device. [Background technology]

[0002] With the advancement of AI (Artificial Intelligence) technology and the expansion of 5G technology, the density of heat generated by electronic devices (heat density) is increasing. It is necessary to manage heat density within an appropriate range to maintain the performance of electronic devices, and the use of two main phenomena, heat transport and heat storage, to manage heat density is being considered. Here, because the local increase in heat density makes it difficult to address the issue by simply increasing heat transport using materials with high thermal conductivity, there is growing interest in storing heat using heat storage materials.

[0003] On the other hand, heat storage materials generally have low heat dissipation performance, so when excess heat is applied that exceeds the amount of heat stored, the temperature rises significantly. Therefore, in order to reduce the heat density of electronic devices while utilizing both heat transport and heat storage, it has been proposed to use a composite material made of a material with high thermal conductivity and a heat storage material.

[0004] For example, Patent Document 1 discloses a solid heat storage material that is a bond in which vanadium dioxide, which is one of the solid heat storage materials, and a high thermal conductivity substance are closely attached to each other. Patent Document 2 discloses a composite heat storage material in which a heat storage material is dispersed and mixed in an inorganic material. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2021 / 230357 [Patent Document 2] JP 2016-79351 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, in conventional composite materials, the distribution of thermally conductive materials is not efficient in contributing to heat dissipation, so a large amount of thermally conductive material must be added to improve thermal conductivity, making it difficult to achieve this while also storing heat.

[0007] In view of the above, an object of the present invention is to provide a material that efficiently dissipates heat and a method for manufacturing the same. Another object of the present invention is to provide an electronic device that efficiently dissipates heat.

[0008] In addition to the above-mentioned objective, the achievement of effects derived from each configuration shown in the description of the embodiment of the invention described below, which cannot be obtained by conventional techniques, can also be positioned as another objective of the disclosure of this specification. [Means for solving the problem]

[0009] The above object can be achieved by the present invention, which is described below. The material of the present invention is a material in which a plurality of particles formed containing a latent heat material that causes a solid-solid phase transition and a heat conductive material having a higher thermal conductivity than the latent heat material are mixed, the volume fraction of the material occupied by the heat conductive material being 20% ​​or more and less than 100%, and the average particle size of the particles being 0.1 μm or more and 40 μm or less. Effect of the Invention

[0010] According to the present invention, it is possible to provide a material that efficiently dissipates heat and a method for producing the same, and also to provide an electronic device that efficiently dissipates heat. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram illustrating an example of the configuration of a material of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a method for producing the materials of Examples 1 to 4. [Diagram 3] 1 is an image observed with a SEM (scanning electron microscope) in Example 1. [Figure 4] 1 is a graph illustrating an example of a radial distribution function in Example 1. [Diagram 5] FIG. 2 is a schematic diagram illustrating an example of a manufacturing method for Comparative Example 1. [Figure 6] 1 is an image of the porous body of Example 5 observed with a SEM (scanning electron microscope). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Note that the disclosure of this specification is not limited to the following embodiments, and various modifications (including organic combinations of each embodiment) are possible based on the spirit of the disclosure of this specification, and are not excluded from the scope of the disclosure of this specification. In other words, configurations that combine each of the embodiments and their modifications described below are all included in the embodiments disclosed in this specification.

[0013] The present inventors investigated the heat dissipation performance of a material (composite material) that contains both a latent heat material, which is a type of heat storage material, and a heat conductive material that has a higher thermal conductivity than the latent heat material. As a result, it was found that the heat dissipation performance is improved when the volume fraction of the heat conductive material in the composite material is 20% or more and less than 100%, and the latent heat material is contained as multiple particles with an average particle size of 0.1 μm or more and 40 μm or less.

[0014] Based on the above findings, further investigations were carried out and it was discovered that heat dissipation performance is improved especially when the thermally conductive material and the latent heat material form a sea-island structure among composite materials. Here, the sea-island structure refers to a state in which one of the two materials forms one or more isolated particles (islands), and the other material forms a structure (sea) that envelops the particles. It was found that composite materials with a sea-island structure in which the latent heat material forms islands and the thermally conductive material forms the sea have high heat dissipation performance.

[0015] The reason why the configuration of the present invention improves heat dissipation performance is presumed to be as follows. Heat generated from a heat source is transported by the thermally conductive material, and is transferred from the thermally conductive material to the latent heat material, where it is stored. Therefore, the thermally conductive material has a continuous structure, and the total surface area of ​​the latent heat material is large, allowing for efficient heat dissipation.

[0016] <First embodiment> The material according to the first embodiment is a material in which a plurality of particles formed containing a latent heat material that undergoes a solid-solid phase transition are mixed with a heat conductive material having a higher thermal conductivity than the plurality of particles containing the latent heat material. By mixing the heat conductive material with the latent heat material, a material with high heat dissipation performance can be provided while utilizing the heat storage by the latent heat material.

[0017] (Material composition) The structure of the material of this embodiment will be described with reference to Fig. 1. Fig. 1 is a schematic diagram for explaining the structure of the material of this embodiment, showing a cross section of the material of this embodiment.

[0018] The material 100 of this embodiment has a structure in which particles 102 formed by including a latent heat material are dispersed substantially uniformly in the thermal conductive material 101 in any cross section. Here, "substantially uniformly dispersed" means that the particles 102 may partially form aggregates, but the radial distribution function of the particles 102 defined by g(r) in the following (Equation 1) approaches 1 asymptotically at infinity (r→∞). g(r) = <n i (r) / dV(r)> (Eq. 1) where n i (r) is the number of particles between the spherical shell at distance r and distance r+dr from a particle i, and dV(r) is the volume of the said spherical shell. Also, in (Equation 1), <> is the n i Therefore, the radial distribution function g(r) represents the probability that another particle exists at a distance r from a certain particle.

[0019] In addition, the smallest distance at which the absolute value of the radial distribution function is a local maximum or a maximum value is defined as the first adjacent distance. When particles are dispersed almost uniformly and the average particle size of the particles is smaller than the first adjacent distance of the radial distribution function, this means that, on average, the particles are not in contact with each other. In other words, the particles are isolated on average, forming a so-called sea-island structure.

[0020] The volume fraction φ of the thermal conductive material 101 in the material of this embodiment 101 can be calculated from the following (Equation 2) and (Equation 3). ρ 100 =m 100 / V 100 ...(Formula 2) ρ 100 =ρ 101 φ 101 +ρ 102 (1-φ 101 )...(Formula 3) where m 100 is the mass of 100 of the material, V 100 is the volume of 100 of the material, ρ 100 , ρ 101 , ρ 102 are the densities of the material 100, the thermal conductive material 101, and the particles 102, respectively. For example, the density of copper is 8.9 [g / cm 3 ], VO2 (vanadium dioxide) is 4.3 [g / cm 3 ].

[0021] The particles 102 are formed containing a latent heat material that undergoes a solid-to-solid phase transition. The latent heat material may be any material with large latent heat, such as vanadium oxide, trititanium pentoxide, dititanium trioxide, or nickel titanium. Of these, the latent heat material is preferably an oxide material containing VO2 (vanadium dioxide). The oxide material is preferably V in which part of the vanadium is replaced with element M (M=at least one selected from the group consisting of tungsten, chromium, molybdenum, niobium, tantalum, osmium, iridium, and ruthenium). 1-n M n O2 is preferred.

[0022] V 1-n Mn O2 is a material whose phase transition temperature changes depending on the type and ratio n of element M. Therefore, by selecting element M and ratio n, the phase transition temperature can be adjusted to a desired temperature range. For example, the phase transition temperature of vanadium dioxide is 68°C, but 0.99 W 0.01 The phase transition temperature of O2 (M = tungsten, n = 0.01) is 39°C.

[0023] The phase transition temperature can also be adjusted to a desired temperature by making the particles 102 porous. For example, the phase transition temperature of vanadium dioxide is about 68° C., but the phase transition temperature of porous vanadium dioxide formed by contacting vanadium dioxide particles with an average size of 200 nm with each other is about 80° C. The change in phase transition temperature caused by forming a porous body is considered to be due to the strain distribution in the particles 102 caused by the particles 102 having a pore structure inside.

[0024] The shape of the particles 102 may be a sphere, a square, a subsquare, or a mixture of these. The particles may be two or more spherical or square particles bonded together. The average particle size of each of the particles 102 in the case of a shape other than a sphere is defined as the average diameter of spheres having the same volume as the volume of each particle. When the average particle size is determined using a two-dimensional image (electron microscope image) such as an electron microscope, it is defined as the average diameter of circles having the same area as the area of ​​the particle. From the viewpoint of improving heat dissipation performance, the particles 102 preferably have an average particle size of 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 20 μm or less, and even more preferably 1 μm or more and 15 μm or less.

[0025] The thermal conductive material 101 may be any material having a higher thermal conductivity than the latent heat material 102, and is not particularly limited, but may be ceramics, metal, carbon material, or the like. Preferably, copper or aluminum is used. The volume fraction of the thermal conductive material 101 in the material 100 is preferably 20% or more and less than 100%, and more preferably 30% or more and 70% or less.

[0026] That is, the material of the present invention is characterized in that the volume fraction of the heat conductive material 101 is 20% or more and less than 100%, and the average particle size of the particles (latent heat material 102) is 0.1 μm or more and 100 μm or less.

[0027] Furthermore, in order to enable efficient heat dissipation, it is preferable that the heat conductive material 101 and the particles 102 including the latent heat material contained in the material 100 form a sea-island structure. In particular, a sea-island structure in which the heat conductive material 101 forms the sea and the particles 102 form the islands allows efficient heat conduction from the heat conductive material 101 to the particles 102, improving the heat dissipation performance of the material 100.

[0028] Here, when the thermally conductive material 101 and the particles 102 form a sea-island structure, the first adjacent distance in the radial distribution function of the particles 102 is larger than the average particle size of the particles 102 in a microscope image (e.g., an SEM image). That is, in order to improve the heat dissipation performance by forming the sea-island structure, it is desirable that the first adjacent distance in the radial distribution function of the particles 102 is larger than the average particle size of the particles 102.

[0029] Furthermore, as a result of the inventor's investigation, it was found that the heat dissipation performance is improved when the thermally conductive material 101 and the particles 102 form a sea-island structure and when at least two particles 102 are spaced apart by a certain distance or more. That is, in order to improve the heat dissipation performance, it is preferable that the radial distribution function of the plurality of particles 102 in an electron microscope image has a first adjacent peak value of 1.1 or more and the value of the radial distribution function asymptotically approaches 1.0 at a distance of 2.0 times or more the first adjacent distance.

[0030] In this case, in order to determine the first adjacent peak of the radial distribution function and the asymptotic value using (Equation 1), at least 500 particles must be formed as images in the microscope image. This number of particles is the number of samples required when assuming that the standard deviation of the radial distribution function value calculated for each particle is about 1.0, the allowable error is at least 0.1 in absolute value, and a 95% confidence interval. The reason why the standard deviation is assumed to be about 1.0 is that when particles are arranged completely randomly, the radial distribution function asymptotically approaches 1.0. In addition, the reason why the allowable error is set to at least 0.1 in absolute value is that when the first adjacent peak is 1.1, it is necessary to be able to determine a peak with a value 0.1 larger than the asymptotic value of 1.0.

[0031] (action) In the material of this embodiment, heat is transported by the thermally conductive material 101, and heat is stored by the latent heat material of the particles 102. If the thermally conductive material 101 is continuous, heat can be transported efficiently, and as a result, heat is dissipated efficiently. In addition, the heat transported to the surface of the particles 102 by the thermally conductive material 101 is stored in the particles 102. Therefore, the larger the total surface area of ​​the particles 102, the larger the heat stored in the particles 102. Therefore, the smaller the particle size of the particles 102, the larger the amount of heat stored. On the other hand, if the particle size is less than 0.1 μm, for example, in the case of vanadium dioxide, the phase transition temperature rises significantly, and the amount of heat stored at the original phase transition temperature becomes small. This decrease in the amount of heat storage occurs when the average particle size is 1 μm or less.

[0032] As a result of intensive research by the inventors, it was found that a large heat storage effect can be obtained if the volume fraction of the heat conductive material 101 to the material 100 is 20% or more and less than 100%, the heat conductive material 101 has a continuous structure, and the particle diameter of the particles 102 is 0.1 μm or more and 100 μm or less. Therefore, it was found that it is possible to provide a material having high heat dissipation performance while utilizing heat storage by a latent heat material.

[0033] <Second embodiment> A method for producing the material of the present invention will be described. The production method according to the present invention includes a mixing step of mixing copper-containing metal particles and vanadium dioxide-containing oxide particles to obtain a mixture, and a sintering step of heating and sintering the mixture. Here, by adjusting the average particle size of the metal particles and oxide particles, which are the materials to be mixed, a material having a structure suitable for improving heat dissipation performance can be produced. In order to produce a material with improved heat dissipation performance, it is preferable that the ratio of the average particle size of the oxide particles to the average particle size of the metal particles is 5.0 or more.

[0034] <Third embodiment> The electronic device of the present invention includes a heat source and the material described in the first embodiment, and is characterized in that the heat source and the material are in direct contact with each other, or the heat source and the material are in contact with each other via a thermally conductive material. By directly or indirectly contacting the heat source with a material with high heat dissipation performance, heat can be dissipated to the outside of the electronic device without concentrating heat around the heat source. Here, the heat source may be any component that increases the temperature of the electronic device, such as a memory or a CPU.

[0035] [Example] The present invention will be described in detail below with reference to specific examples. Note that the present invention is not limited to the configurations or forms of the following examples.

[0036] [Example 1] (Material manufacturing method) In this example, the material shown in Fig. 2 was produced. An example of each production process will be described below with reference to Fig. 2.

[0037] First, 15.8 g of copper particles (201) with an average particle size d1 of 5 μm and 7.7 g of VO2 particles (202) with an average particle size d2 of 30 μm were prepared and mixed (Fig. 2 (1) Mixing). At this time, the ratio of the average particle size of the copper particles 201 to the average particle size of the VO2 particles 202 was 30 μm / 5 μm = 6.0. The particle size of each particle before mixing was determined by a laser diffraction / scattering method. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 300 (Fig. 2 (2) Sintering).

[0038] (Materials Evaluation) The size and mass of the material 300 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 4.8 mm, and the mass was 22.4 g. From the obtained mass and size (volume), the density of the material 200 was calculated to be 6.6 g / cm3 according to (Equation 2). 3 The volume fraction of copper was calculated to be 50% using the calculated density of material 200 and the densities of copper and VO2 (Equation 3). The cross section of the obtained sample was observed using an electron microscope (Figure 3). Energy dispersive X-ray spectroscopy (SEM-EDX) revealed that the areas with low brightness were VO2 and the areas with high brightness were copper.

[0039] This observation image was binarized to determine the center of gravity and area of ​​each particle 302. The diameter of a circle that had the same area as the obtained area (equivalent circle diameter) was obtained to determine the particle size of each particle 302. As a result, it was found that the average particle size was 10 μm and the maximum particle size was 50 μm or less. The reason that the average particle size differs from that of particles 202 before mixing is thought to be due to the densification of the particles during sintering, and because the particle size measured by the laser diffraction / scattering method may include aggregated particles that are captured as a single particle, the particle size was estimated to be larger than that of the image observed by the electron microscope.

[0040] Furthermore, the radial distribution function RDF was calculated from (Equation 1) assuming that each particle 302 exists at the coordinates of the center of gravity of each particle. The result is shown in Figure 4. It was found that the first adjacent distance was 20 μm, the value of the radial distribution function was 1.15 at the first adjacent peak, and it asymptotically approached 1.0 at a distance of 40 μm or more.

[0041] From this, it can be seen that up to the first adjacent distance, particles are concentrated at about 1.1 times the average particle number density of the entire material. From the second adjacent distance onwards, the radial distribution function approaches 1.0, which indicates that this structure is an almost uniform dispersion. In addition, since the first adjacent distance is 20 μm for an average particle size of 10 μm, it is clear that a sea-island structure is formed.

[0042] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 120 W / mK, the latent heat was 103 J / cc, and the phase transition temperature was 69°C.

[0043] [Example 2] (Material manufacturing method) In this embodiment, the particle 202 is V 0.99 W 0.01 A material 300 was produced in the same manner as in Example 1, except that O2 was used.

[0044] First, 17.4 g of copper particles with an average particle size of 5 μm and V 0.99 W 0.01 8.5 g of O2 particles were prepared and mixed. At this time, the average particle size of the copper particles and V 0.99 W 0.01 The ratio of the average particle diameters of the O2 particles was 30 μm / 5 μm = 6.0. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 300.

[0045] (Materials Evaluation) The size and mass of the material 300 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 5.3 mm, and the mass was 24.6 g. From the obtained mass and size (volume), the density of the material 200 was calculated to be 6.6 g / cm3 according to (Equation 2). 3 Also, V 0.99 W 0.01 When O2 was sintered and its density was measured, it was found to be 4.3 [g / cm3], the same as VO2. 3Using these results, the volume fraction of copper calculated from (Equation 3) was 50%. The cross section of the obtained sample was observed by an electron microscope. This observed image was binarized, and the center of gravity of each particle 302 and the area of ​​each particle were determined.

[0046] The diameter of a circle with the same area as the obtained area was calculated, and the particle size of each particle was determined. As a result, it was found that the average particle size was 10 μm and the maximum particle size was 50 μm or less. Furthermore, when the radial distribution function was calculated for the binarized image of the obtained observation image, it was found to be approaching 1.0 at a distance of 40 μm or more. Therefore, it was found that this structure was a nearly uniform dispersion. In addition, since the first adjacent distance was 20 μm for an average particle size of 10 μm, it was found that a sea-island structure was formed.

[0047] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 117 W / mK, the latent heat was 76 J / cc, and the phase transition temperature was 40°C.

[0048] [Example 3] (Material manufacturing method) In this example, material 300 was produced using the same production process as in Example 1, except that the volume fraction of copper particles 201 was changed.

[0049] First, 9.0 g of copper particles with an average particle size of 5 μm and 10.1 g of VO2 particles with an average particle size of 30 μm were prepared and mixed. At this time, the ratio of the average particle size of the copper particles 201 to the average particle size of the VO2 particles 202 was 30 μm / 5 μm=6.0. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered by a spark plasma sintering (SPS) device to obtain a sintered body, material 300.

[0050] (Materials Evaluation) The size and mass of the material 300 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 4.7 mm, and the mass was 18.9 g. From the obtained mass and size (volume), the density of the material 200 was calculated to be 5.7 g / cm3 according to (Equation 2).3 Using these results, the volume fraction of copper calculated from (Equation 3) was 30%. The cross section of the obtained sample was observed by an electron microscope. The observed image was binarized, and the center of gravity of each particle 302 and the area of ​​each particle were determined.

[0051] The diameter of a circle with the same area as the obtained area was calculated, and the particle size of each particle was determined. As a result, it was found that the average particle size was 10 μm and the maximum particle size was 50 μm or less. Furthermore, when the radial distribution function was calculated for the binarized image of the obtained observation image, it was found to be approaching 1.0 at a distance of 30 μm or more. Therefore, it was found that this structure was a nearly uniform dispersion. In addition, since the first adjacent distance was 17 μm for an average particle size of 10 μm, it was found that a sea-island structure was formed.

[0052] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 67 W / mK, the latent heat was 144 J / cc, and the phase transition temperature was 69°C.

[0053] [Example 4] (Material manufacturing method) In this example, material 300 was produced by the same production process as in Example 1, except that the volume fraction of copper particles 201 was changed.

[0054] First, 22.1 g of copper particles with an average particle size of 5 μm and 4.6 g of VO2 particles with an average particle size of 30 μm were prepared and mixed. At this time, the ratio of the average particle size of the copper particles to the average particle size of the VO2 particles was 30 μm / 5 μm = 6.0. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 300.

[0055] (Materials Evaluation) The size and mass of the material 300 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 5.0 mm, and the mass was 26.5 g. From the obtained mass and size (volume), the density of the material 200 was calculated to be 7.5 g / cm3 according to (Equation 2). 3Using these results, the volume fraction of copper calculated from (Equation 3) was 70%. The cross section of the obtained sample was observed with an electron microscope. This observed image was binarized, and the center of gravity of each particle 302 and the area of ​​each particle were obtained. The diameter of a circle having the same area as the obtained area was calculated, and the particle size of each particle was determined.

[0056] As a result, it was found that the average particle size was 10 μm and the maximum particle size was 50 μm or less. Furthermore, when the radial distribution function was calculated for the binarized image of the obtained observation image, it was found to be approaching 1.0 at a distance of 50 μm or more. Therefore, it was found that this structure is a nearly uniform dispersion. In addition, since the first adjacent distance is 25 μm for an average particle size of 10 μm, it was found that a sea-island structure was formed.

[0057] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 230 W / mK, the latent heat was 62 J / cc, and the phase transition temperature was 69°C.

[0058] [Example 5] (Material manufacturing method) In this example, a material 300 was produced in the same manner as in Example 1, except that porous VO 2 particles were used for the particles 202.

[0059] First, VO2 particles with a particle size of 200 nm were milled in a planetary ball mill (0.2 mm beads in air) and sieved through a #125 mesh to obtain porous VO2 particles (Figure 6).

[0060] 4.6 g of the obtained porous VO2 particles with an average particle size of 30 μm and 15.8 g of copper particles with an average particle size of 5 μm were prepared and mixed. At this time, the ratio of the average particle size of the copper particles to the average particle size of the porous VO2 particles was 30 μm / 5 μm = 6.0. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 300.

[0061] (Materials Evaluation) The size and mass of the material 300 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 4.9 mm, and the mass was 19.9 g. From the obtained mass and size (volume), the density of the material 200 was calculated to be 5.7 g / cm3 according to (Equation 2). 3 In addition, the porous VO2 particles were sintered and their density was measured, and found to be 2.6 g / cm 3 Using these results, the volume fraction of copper calculated from (Equation 3) was 50%. The cross section of the obtained sample was observed by an electron microscope. This observed image was binarized, and the center of gravity of each particle 302 and the area of ​​each particle were obtained.

[0062] The diameter of a circle with the same area as the obtained area was calculated, and the particle size of each particle was determined. As a result, it was found that the average particle size was 10 μm and the maximum particle size was 50 μm or less. Furthermore, when the radial distribution function was calculated for the binarized image of the obtained observation image, it was found to be approaching 1.0 at a distance of 40 μm or more. Therefore, it was found that this structure was a nearly uniform dispersion. In addition, since the first adjacent distance was 20 μm for an average particle size of 10 μm, it was found that a sea-island structure was formed.

[0063] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 100W / mK, the latent heat was 58J / cc, and the phase transition temperature was 80℃.

[0064] [Comparative Example 1] (Material manufacturing method) In this comparative example, material 600 was produced by the same manufacturing process as in Example 1, except that the ratio of the particle size of the copper particles to the particle size of the VO2 particles was set to less than 1. Figure 5 shows a schematic diagram of the manufacturing method.

[0065] First, 15.0 g of copper particles with an average particle size of 30 μm and 7.3 g of VO2 particles with an average particle size of 5 μm were prepared and mixed (Fig. 5 (1) Mixing). At this time, the ratio of the average particle size of the copper particles 501 to the average particle size of the VO2 particles 502 was 5 μm / 30 μm = 0.17. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 600 (Fig. 5 (2) Sintering).

[0066] (Materials Evaluation) The size and mass of the material 600 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 5.0 mm, and the mass was 23.0 g. From the obtained mass and size (volume), the density of the material 600 was calculated to be 6.5 g / cm3 according to (Equation 2). 3 In addition, the volume fraction of copper calculated from (Equation 3) using the calculated density of material 600 and the densities of copper and VO2 was 48%.

[0067] The cross section of the obtained sample was observed by an electron microscope. From this observation image, it was found that the latent heat material 602 had a mixed structure in which islands were not formed. Here, the mixed structure means a state in which it is not possible to clearly distinguish which of the latent heat material 602 and the thermal conductive material 601 is the sea and which is the island. In particular, in this Comparative Example 1, the latent heat material 602 had a structure in which islands were not formed.

[0068] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 70 W / mK, the latent heat was 97 J / cc, and the phase transition temperature was 69°C.

[0069] [Comparative Example 2] (Material manufacturing method) In this comparative example, material 600 was produced by the same manufacturing process as in comparative example 1, except that the volume fraction of copper particles 501 was changed.

[0070] First, 9.6 g of copper particles with an average particle size of 30 μm and 10.7 g of VO2 particles with an average particle size of 5 μm were prepared and mixed. At this time, the ratio of the average particle size of the copper particles to the average particle size of the VO2 particles was 5 μm / 30 μm = 0.17. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 600.

[0071] (Materials Evaluation) The size and mass of the material 600 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 5.0 mm, and the mass was 20.1 g. From the obtained mass and size (volume), the density of the material 600 was calculated to be 5.7 g / cm3 according to (Equation 2). 3 The volume fraction of copper calculated from (Equation 3) using the calculated density of material 600 and the densities of copper and VO2 was 30%. The cross section of the obtained sample was observed with an electron microscope. From this observation image, it was found that the latent heat material 602 had a mixed structure that did not form islands.

[0072] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 30 W / mK, the latent heat was 120 J / cc, and the phase transition temperature was 69°C.

[0073] [Comparative Example 3] (Material manufacturing method) In this comparative example, material 600 was produced by the same manufacturing process as in comparative example 1, except that the volume fraction of copper particles 501 was changed.

[0074] First, 22.1 g of copper particles with an average particle size of 30 μm and 4.6 g of VO2 particles with an average particle size of 5 μm were prepared and mixed. At this time, the ratio of the average particle size of the copper particles 501 to the average particle size of the VO2 particles 502 was 5 μm / 30 μm = 0.17. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered by a spark plasma sintering (SPS) device to obtain a sintered body, material 600 [Figure 5 (2) Sintering].

[0075] (Materials Evaluation) The size and mass of the material 600 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 5.0 mm, and the mass was 26.5 g. From the obtained mass and size (volume), the density of the material 600 was calculated to be 7.5 g / cm3 according to (Equation 2). 3 The volume fraction of copper calculated from (Equation 3) using the density of material 600 and the densities of copper and VO2 was 70%. The cross section of the obtained sample was observed with an electron microscope. From this observation image, it was found that the latent heat material 602 had a mixed structure that did not form islands.

[0076] The thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 170 W / mK, the latent heat was 52 J / cc, and the phase transition temperature was 69°C.

[0077] [Comparative Example 4] (Material manufacturing method) In this comparative example, material 300 was produced by the same manufacturing process as in Example 1, except that the volume fraction of copper particles 201 was reduced to less than 20%.

[0078] First, 5.7 g of copper particles with an average particle size of 5 μm and 11.7 g of VO2 particles with an average particle size of 30 μm were prepared and mixed. At this time, the ratio of the average particle size of the copper particles to the average particle size of the VO2 particles was 30 μm / 5 μm = 6.0. Next, the mixed particles were placed in a cylindrical mold with a diameter of 30 mm and sintered using a spark plasma sintering (SPS) device to obtain a sintered body, material 300.

[0079] (Materials Evaluation) The size and mass of the material 300 prepared as described above were measured. As a result, the average diameter was 30 mm, the average thickness was 4.6 mm, and the mass was 16.9 g. From the obtained mass and size (volume), the density of the material 200 was calculated to be 5.2 g / cm3 according to (Equation 2). 3 Using these results, the volume fraction of copper calculated from (Equation 3) was 19%.

[0080] The cross section of the obtained sample was observed by an electron microscope. This observation image was binarized to determine the center of gravity of each particle 302 and the area of ​​each particle. The diameter of a circle having the same area as the obtained area was obtained to determine the particle size of each particle. As a result, it was found that the average particle size was 10 μm and the maximum particle size was 50 μm or less. Furthermore, when the radial distribution function was calculated for the binarized image of the obtained observation image, it was found that the first adjacent distance was 10 μm. Since the first adjacent distance was 10 μm while the average particle size was 10 μm, it was found that the structure was not an island-sea structure but a matrix structure in which the particles 302 were continuously connected.

[0081] Thermal properties were measured by the xenon flash method for thermal conductivity and the differential scanning calorimetry (DSC) method for latent heat, and the thermal conductivity was 15 W / mK, the latent heat was 5.3 J / cc, and the phase transition temperature was 69°C.

[0082] The above results are shown in Table 1.

[0083] [Table 1]

[0084] As shown in Table 1, when comparing the thermal conductivity of materials with the same volume fraction of thermal conductive material, the examples always had a higher thermal conductivity than the comparative examples. That is, the configuration of the present invention can improve the thermal conductivity and improve the heat dissipation performance even when the volume fraction of the thermal conductive material is constant. In other words, the material of the present invention can improve the heat dissipation performance of a material containing a latent heat material by having a volume fraction of the thermal conductive material of 20% or more and less than 100%, and an average particle size of the particles of 0.1 μm or more and 100 μm or less.

[0085] Although the embodiments and examples of the present invention have been specifically described, the present invention is not limited to the above-mentioned embodiments. The present invention can be modified in various ways based on the technical ideas. For example, the numerical values ​​and components given in the above-mentioned embodiments are merely examples. Numeric values ​​and components different from these may be used as necessary.

[0086] By using the materials of the above-mentioned embodiments and examples, a higher heat dissipation performance can be obtained than that of existing latent heat materials, so that both heat dissipation and heat storage can be achieved. Therefore, since heat can be dissipated without providing a separate heat path for heat dissipation, heat management devices (heat sinks, heat storage devices, etc.) can be miniaturized. For example, it can be used for thermal management of small 5G devices, edge AI devices, IoT devices, etc. It can also be expected to be used as a device for thermal management of high-density heat sources such as high-definition video cameras with high thermal density such as 8K and 12K, medical equipment using X-rays, automobiles and railway vehicles, industrial equipment and office equipment, and high-performance computing systems. In addition, since the present invention can improve the heat dissipation performance of the heat storage material, it can be applied to a wide range of fields other than those described above.

[0087] The disclosure of this embodiment includes the following configurations and methods.

[0088] (Configuration 1) A plurality of particles formed including a latent heat material that undergoes a solid-solid phase transition; A material including a thermally conductive material having a higher thermal conductivity than the latent heat material, The volume fraction of the thermally conductive material in the material is 20% or more and less than 100%, The material has an average particle size of 0.1 μm or more and 40 μm or less.

[0089] (Configuration 2) The material according to configuration 1, characterized in that the volume fraction of the material occupied by the thermally conductive material is 30% or more and 70% or less.

[0090] (Configuration 3) 3. The material according to claim 1 or 2, wherein the latent heat material is an oxide material containing vanadium dioxide.

[0091] (Configuration 4) The material according to configuration 3, wherein the oxide material includes at least one selected from the group consisting of tungsten, chromium, molybdenum, niobium, tantalum, osmium, iridium, and ruthenium.

[0092] (Configuration 5) 5. The material according to any one of claims 1 to 4, wherein the particles are porous.

[0093] (Configuration 6) The material according to any one of configurations 1 to 5, wherein the thermally conductive material and the plurality of particles form a sea-island structure.

[0094] (Configuration 7) The material according to any one of configurations 1 to 6, wherein the thermally conductive material is a sea, and the plurality of particles are islands, forming a sea-island structure.

[0095] (Configuration 8) The material described in any one of claims 1 to 7, characterized in that the first adjacent distance of the radial distribution function of the plurality of particles in the electron microscope image is larger than the average particle size of the plurality of particles in the electron microscope image.

[0096] (Configuration 9) 9. The material described in any one of configurations 1 to 8, characterized in that in an electron microscope image, the radial distribution function of the plurality of particles has a value that asymptotically approaches 1.0 at a distance that is 2.0 times or more the first adjacent distance.

[0097] (Configuration 10) The material described in any one of configurations 1 to 8, characterized in that in a radial distribution function of the plurality of particles in an electron microscope image, the value of a first adjacent peak is 1.1 or more, and the value of the radial distribution function approaches 1.0 at a distance of 2.0 times or more the first adjacent distance.

[0098] (Configuration 11) 11. An electronic device comprising the material according to any one of configurations 1 to 10, the material being in contact with a heat source directly or via a heat conductive material.

[0099] (Method 1) A mixing step of mixing metal particles containing copper and oxide particles containing vanadium dioxide to obtain a mixture; A sintering step of heating the mixture to sinter it, A method for producing a material, characterized in that the ratio of the average particle size of the oxide particles to the average particle size of the metal particles is 5.0 or more. [Explanation of symbols]

[0100] 100, 300 materials 101, 301 Thermal Conductive Materials 102, 302 Particles containing latent heat material 201 Particles containing thermally conductive materials 202 Particles with latent heat material

Claims

1. a plurality of particles formed including a latent heat material that undergoes a solid-solid phase transition; A material including a thermally conductive material having a higher thermal conductivity than the latent heat material, The volume fraction of the thermally conductive material in the material is 20% or more and less than 100%, The material has an average particle size of 0.1 μm or more and 40 μm or less.

2. The material according to claim 1 , characterized in that the volume fraction of the material occupied by the thermally conductive material is 30% or more and 70% or less.

3. 10. The material of claim 1, wherein the latent heat material is an oxide material comprising vanadium dioxide.

4. 4. The material of claim 3, wherein the oxide material comprises at least one selected from the group consisting of tungsten, chromium, molybdenum, niobium, tantalum, osmium, iridium, and ruthenium.

5. The material of claim 1, wherein the particles are porous.

6. The material of claim 1 , wherein the thermally conductive material and the plurality of particles form an islands-in-a-sea structure.

7. The material according to claim 1 , wherein the thermally conductive material is a sea, and the plurality of particles are islands, forming a sea-island structure.

8. 2. The material according to claim 1, wherein a first adjacent distance in a radial distribution function of the plurality of particles in the electron microscope image is greater than an average particle size of the plurality of particles in the electron microscope image.

9. 2. The material according to claim 1, wherein in an electron microscope image, the radial distribution function of the plurality of particles asymptotically approaches 1.0 at a distance of 2.0 times or more the first adjacent distance.

10. 2. The material according to claim 1, characterized in that in a radial distribution function of the plurality of particles in an electron microscope image, the value of a first adjacent peak is 1.1 or more, and the value of the radial distribution function asymptotically approaches 1.0 at a distance of 2.0 times or more the first adjacent distance.

11. 11. An electronic device comprising the material according to claim 1, wherein the material is in contact with a heat source directly or via a thermally conductive material.

12. A mixing step of mixing metal particles containing copper and oxide particles containing vanadium dioxide to obtain a mixture; A sintering step of heating the mixture to sinter it, A method for producing a material, characterized in that the ratio of the average particle size of the oxide particles to the average particle size of the metal particles is 5.0 or more.

Citation Information

Patent Citations

  • Composite heat-storing material

    JP2016079351A

  • Solid heat storage material having regulated thermal conductivity and composite

    WO2021230357A1